The role of ECOWAS in settling conflicts in West Africa / Liberia as a model (Journal of the College of Basic Education, 2022)
The Ecowas Group was established in the western part of Africa in May 1975 through the Lagos Agreement, which was signed by 15 countries in Africa, and all this after the efforts made by some countries over a number of years to achieve security, economic and political stability in the region.Although Ecowas is basically economic in nature, some of the founders of the organization gave some opinions to introduce the political and security matters of the region within the organization, and this is after the emergence of some groups threatening security in the region, which caused a lot of civil wars that left a lot of human losses and a large number of people died. Civilians because of these wars they have nothing to do with, and after this they agreed to